PEMANFAATAN CHROMEBOOK DALAM PROSES PEMBELAJARAN PAI BERBASIS KURIKULUM MERDEKA - HASANAH, ZUNIATUL; MARYAM, QORRIE AINA (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
ABSTRACT This study aims to explore the use of technology in learning, especially in the context of Islamic Religious Education (PAI) and Character Education in accordance with the Merdeka Curriculum. The purpose of this paper is to analyze the impact of Chromebook use on learning, including increasing collaboration, creativity, and student understanding of the material. This study uses a descriptive qualitative approach with a case study model. The results and discussion of this study found that the use of Chromebooks in learning Islamic Religious Education (PAI) and Character Education according to the Merdeka Curriculum showed a significant positive impact. Chromebooks facilitate access to digital learning resources such as the Qur'an and Google Workspace and Quizizz applications, which enhance student collaboration and creativity.The use of Google Docs and Slides supports group work, while applications like Quizizz reinforce students' understanding through interactive learning. Additionally, Chromebooks contribute to the development of Pancasila Student Profile values through research and collaboration related to religion and culture.Project-based learning and personalization of learning are increasingly facilitated by these devices, supporting students to learn at their own pace. Despite technical challenges, the right strategies can overcome these problems, making Chromebooks an effective tool for learning under the Merdeka Curriculum. The study concludes that the integration of Chromebooks in Islamic Religious Education (PAI) and Character Education learning supports the implementation of the Merdeka Curriculum by enriching teaching materials and enhancing student collaboration. Although challenges such as technical constraints and human resource readiness exist, Chromebook usage can increase students' active participation, deepen material comprehension, and develop digital skills and character traits relevant to modern demands. To maximize its benefits, improvements in infrastructure and further teacher training are necessary. Future research can explore the long-term impact of Chromebook usage on student competency development. ABSTRAK Kajian ini bertujuan untuk mengeksplorasi pemanfaatan teknologi dalam pembelajaran, khususnya dalam konteks Pendidikan Agama Islam (PAI) dan Budi Pekerti sesuai dengan Kurikulum Merdeka. Tujuan penulisan ini adalah untuk menganalisis dampak penggunaan Chromebook terhadap pembelajaran, termasuk peningkatan kolaborasi, kreativitas, dan pemahaman materi siswa. Kajian ini menggunakan pendekatan kualitatif deskriptif dengan model studi kasus. Hasil dan pembahasan kajian ini menemukan bahwa Pemanfaatan Chromebook dalam pembelajaran PAI dan Budi Pekerti sesuai Kurikulum Merdeka menunjukkan dampak positif yang signifikan. Chromebook memfasilitasi akses ke sumber belajar digital seperti Al-Qur'an serta aplikasi Google Workspace dan Quizizz, yang meningkatkan kolaborasi dan kreativitas siswa. Penggunaan Google Docs dan Slides mendukung kerja kelompok, sementara aplikasi seperti Quizizz memperkuat pemahaman siswa melalui pembelajaran interaktif. Chromebook juga membantu pengembangan nilai-nilai Profil Pelajar Pancasila melalui riset dan kolaborasi terkait agama dan budaya. Pembelajaran berbasis proyek dan personalisasi pembelajaran semakin difasilitasi dengan perangkat ini, mendukung siswa untuk belajar sesuai kecepatan mereka. Meskipun ada tantangan teknis, strategi yang tepat dapat mengatasi masalah ini, menjadikan Chromebook alat efektif untuk pembelajaran berbasis Kurikulum Merdeka. Kesimpulan dari penelitian ini menunjukkan bahwa pemanfaatan Chromebook dalam pembelajaran Pendidikan Agama Islam (PAI) dan Budi Pekerti mendukung penerapan Kurikulum Merdeka dengan memperkaya materi ajar dan meningkatkan kolaborasi antar siswa. Meskipun menghadapi kendala teknis dan kesiapan sumber daya manusia, penggunaan Chromebook dapat meningkatkan partisipasi aktif siswa, memperdalam pemahaman materi, dan mengembangkan keterampilan digital serta karakter yang relevan dengan tuntutan zaman. Untuk memaksimalkan manfaatnya, perlu perbaikan infrastruktur dan pelatihan lanjutan bagi guru. Penelitian lebih lanjut dapat mengeksplorasi dampak jangka panjang penggunaan Chromebook terhadap perkembangan kompetensi siswa.